Current approaches for neoadjuvant chemotherapy in breast cancer - Connolly, Roisin (2013)
Compared to adjuvant chemotherapy, the administration of the same regimen in the neoadjuvant setting provides women with identical improvements in disease free and overall survival. Neoadjuvant chemotherapy may offer benefits to properly selected women such as broadening surgical options and enhancing the likelihood of breast conservation. Assessment of response to neoadjuvant chemotherapy provides women with an individualized estimate of prognosis. For example, a woman who achieves a complete pathological response following neoadjuvant chemotherapy has a very low risk of recurrence compared to a woman with similar tumor characteristics and a large residual disease. In this review we will provide a historical perspective and discuss the aims of neoadjuvant chemotherapy in primary operable breast cancer; as well as appropriate patient selection, treatment strategies, response monitoring, and postoperative care. We will also discuss the attractiveness of this approach to study the mechanism of action of standard and novel agents, and the role of predictive biomarkers of response to treatment and outcomes.